Reader’s Reception Toward Love Obsession In Edgar Allan Poe’s “Ligeia”: A Case Study of English Students At Andalas University - Febrin, Nada Aprilia (Linguistika Kultura, 2022)
This thesis discusses the readers’ responses to the theme of obsession with love in “Ligeia,” written by an American writer, Edgar Allan Poe. Through Wolfgang Iser’s reader-response theory, this study analyzes readers’ responses and the value of a literary work according to the readers of the literary works discussed, namely the short story “Ligeia,” factors that form the background of the responses given by readers. The results of the analysis show that the reader’s acceptance of the story is influenced by the reader’s ability to understand the language elements of literary works and their knowledge of vocabulary and the reader’s personal experience, especially the experience of love relationships. In terms of the effect that readers felt on “Ligeia,” the results showed that readers received positive ratings. They rated this work as new and unique experiences.